The surgical management of vault prolapse : a reappraisal with and assessment of the sacrospinous colpopexy and sacrospinous cervicopexy - Slack, Mark Clifford (Department of Obstetrics and Gynaecology, 2017)
The study was undertaken to assess the results of the sacrospinous colpopexy procedure for the treatment of vault prolapse following hysterectomy. It was also to assess the results of the procedure in the treatment of marked uterovaginal prolapse and to compare its role in a group undergoing hysterectomy with a group in whom the uterus was conserved. A prospective study was undertaken between December 1991 and December 1992. Forty women with vm1lt prolapse following hysterectomy were included in one group. All these patients underwent posterior vaginal repair, enterocele sac obliteration and sacrospinous colpopexy. In 25 patients an anterior vaginal repair with sub urethral buttressing sutures was also perfom1ed. A long-needle bladder neck suspension operation was included for three women with coexistent stress incontinence. The mean follow-up period was six months. The success rate was 92%. Of the three failures one underwent a successful repeat sacrospinous colpopexy and repair. The main long-term complication was cystocele formation. A further 24 women with marked uterovaginal prolapse were also included. All women underwent anterior and posterior vaginal repairs, enterocele sac obliteration and sacrospinous ligament fixation. In 13 patients a vaginal hysterectomy was performed and in 11 the uterus was conserved. In the hysterectomy group the follow-up was four months. Although there have been no failures, one woman had developed a small asymptomatic cystocele. Follow-up in the group with uterine preservation was three and a half months. A gain, no failures were seen but three women had developed small asymptomatic cystoceles. There were no differences between the groups apart from a significantly shorter operating time in the patients who did not undergo hysterectomy. The sacrospinous colpopexy is effective in the treatment of vault prolapse. It avoids major abdominal surgery: and allows the surgeon to correct coexistent cystocele and rectocele. The procedure is a useful adjuvent to vaginal repair for marked degrees of uterovaginal prolapse, resulting in a well-supported vagina in the correct anatomical position.